Some Aspects of Modern Bandleader-Choral Preparations of Teachers of Musical Art - Maryna Yarova (Pedagogical Discourse, 2013)
Pedagogical factors and conformities to law, that characterize a process and maintenance of studies, are considered, a polemic is conducted in the discussion of the programs and textbooks, that had for an object maximum to bring down errors and failures in studies. The special attention applies on that, what place in an educational process must and can occupy various facilities of studies, first of all - textbooks, reading-books and educational secret services, conformities to law, that determine success of flowing of educational process, are determined. It all goes to show that the authors of textbooks in a marked period worked on that studies of the church singing to do a meaningful factor education of children, them cultural development, attaching to the high cultural values.